2014
DOI: 10.4103/0975-9476.128857
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of normal individuals classified on the basis of human dosha prakriti

Abstract: Background:Human variations related to immune response and disease susceptibility is well-documented in Ayurveda. Prakriti (body constitution) is the basic constitution of an individual established at the time of birth and distinguishes variations, into three broad phenotype categories such as vata, pitta and kapha. Variation in immune response is often attributed to and measured from the difference in cluster differentiation (CD) markers expressed in lymphocytes. Currently, there are no reports available on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…We have reported a higher level of expression of CD14 markers in pitta and CD25 and CD56 in kapha prakriti , the later correlates with higher immune response observed in individuals with kapha prakriti. [ 36 ] These observations are consistent with what is described in ayurvedic texts.…”
Section: Discussionsupporting
confidence: 90%
“…We have reported a higher level of expression of CD14 markers in pitta and CD25 and CD56 in kapha prakriti , the later correlates with higher immune response observed in individuals with kapha prakriti. [ 36 ] These observations are consistent with what is described in ayurvedic texts.…”
Section: Discussionsupporting
confidence: 90%
“…Gene expression analyses performed among the three prakriti have also identified biochemical and hematological differences [ 20 ]. Previously we have showed differences in expression of cluster differentiation markers CD14, CD25 and CD56 among prakriti phenotypes by immunophenotyping [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concept of Prakriti in Ayurveda and its relationship with genomics was hypothesized over a decade ago 6 . Subsequent studies have attempted to correlate Prakriti classification with genetic information and association of single nucleotide polymorphisms (SNPs) in HLA-DRB1 7 , CYP2C19 8 , EGLN1 9 , inflammatory and oxidative stress related genes 10 , CD markers for various blood cells 11 12 , DNA methylation alterations 13 and risk factors of cardiovascular or inflammatory diseases have been reported 14 . While these studies have shown the association of specific genes with the phenotype of a particular Prakriti , the association of genomic variations with Prakriti classification was lacking.…”
mentioning
confidence: 99%